Pigmented pathological type and depth of follicular extension as predictors of treatment failure in 5-aminolevulinic acid photodynamic therapy for actinic keratosis: A retrospective, matched nested case-control study - Qinyuan Zhu; Huyan Chen; Jing Luan; Qiong Huang; Lianjun Chen; Wenyu Wu; Shujun Chen (Photodiagnosis and Photodynamic Therapy)
Background: While 5-Aminolevulinic acid photodynamic therapy (ALA-PDT) is widely used to treat actinic keratosis (AK), treatment resistance and recurrence after ALA-PDT remain clinical challenges. Methods: This single-site, retrospective, matched case-control study included 119 patients with histologically confirmed AK to identify clinical and pathological predictors for effectiveness of ALA-PDT. Patients received four consecutive ALA-PDT sessions at intervals of 1 or 2 weeks. Initial complete clearance (ICC) at 3 months and sustained complete clearance (SCC) at 12 months were assessed. Case patients were those with treatment-resistant or recurrent AK, matched with controls based on age, sex, and the treatment date. Baseline characteristics were collected and compared between the case and control groups. Results: ICC at 3 months was achieved in 106 out of 119 patients (89.07%), with 65 out of 82 patients (79.27%) maintaining SCC at 12 months. Pigmented AK emerged as an independent predictor of treatment resistance (OR=44.05, p=0.00). Furthermore, follicular extension to the isthmus or deeper was significantly associated with recurrence within 1 year (OR=17.26, p=0.00). Conclusion: Pigmented AK and AK with follicular extension to the isthmus or deeper may serve as independent predictors of treatment resistance and recurrence, respectively. These findings highlight the importance of these specific features when assessing prognosis and tailoring treatment strategies for individual AK patients.